REKOMENDASI DESAIN SISTEM PEMBUMIAN PERALATAN GEDUNG KANKER RUMAH SAKIT BALI MANDARA DENGAN KAJIAN PERBANDINGAN PEMBERIAN ZAT ADITIF GARAM DAN BENTONIT - Harta Narayana, Made Agus Putra; Pramana Putra, I Made Randi Dwi; Alit Swamardika, Ida Bagus; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUM, 2025)
The issue faced at Bali Mandara Hospital is that the sandy soil texture has a relatively high soil resistivity, making it difficult to create a grounding system with low resistance values. One way to reduce soil resistivity is by adding additives such as salt and bentonite. This study aims to determine the effectiveness of these additives in reducing soil resistivity. The results show that the soil resistivity without additives is 33.912 ????.m with a measurement value of 0.27 ohms. With the addition of salt, the soil resistivity decreases to 30.144 ????.m (a reduction of 11.1%), while with the addition of bentonite, it decreases to 20.096 ????.m (a reduction of 40.7%). The recommended grounding system for Bali Mandara Hospital is the single rod type without using additives, with a grounding resistance of 0.941886 ohms at a depth of 50 meters.